1997
DOI: 10.2337/diab.46.8.1354
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Hyperglycemia Predict Coronary Heart Disease Events in Middle-Aged Patients With NIDDM

Abstract: Patients with NIDDM are at increased risk for coronary heart disease (CHD). However, information on the predictive value of cardiovascular risk factors and the degree of hyperglycemia with respect to the risk for CHD in diabetic patients is still limited. Therefore, we carried out a prospective study on risk factors for CHD, including a large number of NIDDM patients. At baseline, risk factor levels of CHD were determined in 1,059 NIDDM patients (581 men and 478 women), aged from 45 to 64 years. These patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(103 citation statements)
references
References 0 publications
5
94
1
3
Order By: Relevance
“…8,18,37,38,39 Entretanto, em relação ao LDL-colesterol, os dados da literatura são menos conclusivos, mas a maioria dos pacientes diabéticos possui taxas elevadas de LDL-colesterol. De acordo com os resultados do Third National Health and Nutrition Examination Survey (NHANES III), 40 por exemplo, 84,6% dos pacientes com DM tipo 2 têm os níveis de LDL-colesterol acima do ótimo (100mg/dL).Neste estudo, também observamos valores médios de LDL-colesterol acima do recomendado (139,28 e 147,98 mg/dL) para os grupos Controle e Treinado, respectivamente.…”
Section: Discussionunclassified
“…8,18,37,38,39 Entretanto, em relação ao LDL-colesterol, os dados da literatura são menos conclusivos, mas a maioria dos pacientes diabéticos possui taxas elevadas de LDL-colesterol. De acordo com os resultados do Third National Health and Nutrition Examination Survey (NHANES III), 40 por exemplo, 84,6% dos pacientes com DM tipo 2 têm os níveis de LDL-colesterol acima do ótimo (100mg/dL).Neste estudo, também observamos valores médios de LDL-colesterol acima do recomendado (139,28 e 147,98 mg/dL) para os grupos Controle e Treinado, respectivamente.…”
Section: Discussionunclassified
“…The RR for the highest quartile of non-HDL cholesterol was significantly higher than that for LDL cholesterol: 2.34 (95% CI 1.26 -4.43) vs. 1.74 (0.99 -3.06). In a Finish cohort study (25), 1,059 middleaged men and women with type 2 diabetes were followed for 7 years, and it was found that higher levels of non-HDL cholesterol were independently associated with a twofold increase in the risk for CHD death or morbidity, although there was no direct comparison between LDL and non-HDL cholesterol for the predictive values of CHD. In the Strong Heart Study cohort (26) of 2,108 AmericanIndian men and women aged 45-74 years with diabetes, the hazard ratios for the highest tertile of non-HDL cholesterol were higher than those for LDL cholesterol among both diabetic men and women, although the CIs were overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, a substantial number of reports have indicated that ApoB and non-HDL-cholesterol are better predictors than LDL-cholesterol in people with diabetes [16][17][18][19]. Few studies have been conducted, however, to compare non-HDL-cholesterol with ApoB [18,19]; the studies that have been reported were restricted to North America, and the results were mixed.…”
Section: Introductionmentioning
confidence: 99%